Power Allocation with Meta-heuristic Algorithms for Indoor MIMO-NOMA Based VLC Systems - Altunbas, Yasin; Turk, Kadir (Wireless personal communications, 2024)
Visible light communication (VLC) is a form of short-range wireless optical communication that uses light in the visible band for both communication and illumination. The limited switching frequencies of light-emitting diodes (LEDs), which are mostly preferred as transmitters in VLC systems, adversely affect the speed of communication. Non-orthogonal multiple access (NOMA) as an access method, and multiple-input multiple-output (MIMO) are used in VLC systems to raise the sum rate. Several methods have been proposed in the literature to determine needed power allocation coefficients for indoor MIMO-NOMA based VLC systems. In this study, meta-heuristic optimization algorithms are proposed to determine the power allocation coefficient that are subject to various constraints including fairness. The numeric results demonstrate the superiority of meta-heuristic methods over sum rate performance. In cases where the user signal strength values differ and the number of users increases, or in other words, the solution becomes more complex, the sum rate acquired by traditional methods reduces, whereas the sum rate using the suggested methods almost does not change and stays high.